Non-linear relationships between the BMI and physical fitness in Polish adolescents - Janusz Kwieciński; Jan M. Konarski; Ryszard Strzelczyk; Magdalena Krzykała; Agata Konarska; Sylwia Bartkowiak; Vitor Lopes; Robert M. Malina (Taylor & Francis Group, 2018)
Background: Comparisons of physical fitness in normal weight and overweight/obese youth generally highlight the negative consequences of an elevated BMI. In contrast, several studies of children and adolescents highlight the importance of variation in indicators of physical fitness across the full spectrum of BMIs from low through high. Aim: The purpose of the study was to evaluate relationships between specific physical fitness items and the BMI among youth. Subjects and methods: Height, weight and six physical fitness tests were measured in 1239 males and 903 females, aged 13-16 years; BMI (kg/m2) was calculated. Fitness tests were compared by weight status using sex-specific MANCOVAs, controlling for age. Sex-specific quadratic regressions of each fitness item on the BMI were also calculated. Results: The sprint, standing long jump and shuttle run indicated better performances in normal than in thin and overweight/obese boys; the latter groups did not differ. Thin and normal weight boys performed better than overweight/obese boys in sit-ups and distance run. Among girls, sit-ups differed as follows: normal > thin > overweight/obese. Thin and normal weight girls performed better than overweight/obese girls in the jump, distance run and shuttle run. Normal weight girls were faster in the sprint than the overweight/obese. The quadratic regressions indicated significant non-linear relationships between the BMI and all fitness items among boys and in four items among girls. Conclusion: Performances on fitness tests varied with weight status. Relationships between performances and the BMI were curvilinear except for the distance run and flexibility in girls.